Prizes and Incentives in Elimination Tournaments - Rosen, Sherwin (American Economic Review, 1986)
Contestants who succeed in attaining high ranks in elimination career ladders rest on their laurels in attempting to climb higher, unless top-ranking prizes are given a disproportionate weight in the purse. A large first-place prize gives survivors something to shoot for, independent of past performances and accomplishments.